Humanitarian Islam or Board of Peace? Nahdlatul Ulama’s Perspective on Resolving the Palestinian Crisis - Aliyah Nabila Zahra (Besari: Journal of Social and Cultural Studies, 2026)
The ongoing humanitarian crisis in the Occupied Palestinian Territory is deeply rooted in weaponized religious and cultural narratives that justify exclusion and territorial domination. This article explores the role of Humanitarian Islam, proposed by Indonesia’s Nahdlatul Ulama (NU) and the R20 International Summit of Religious Authorities (ISORA), in offering theological and social frameworks to mediate this conflict. By emphasizing universal compassion (rahmah) and equal citizenship (al-muwatinun), Humanitarian Islam counters divisive sacred narratives to foster peacebuilding grounded in human dignity. Using a qualitative analytical approach, this research examines the mechanisms of recontextualization in Islamic jurisprudence (fiqh) applied to the Palestinian crisis. The study argues that by dismantling obsolete legal categories like kafir (infidel) and aligning faith with the UN Charter, Humanitarian Islam provides a sustainable alternative to technocratic peace models. Krisis kemanusiaan yang sedang berlangsung di Wilayah Terjajah Palestina berakar kuat pada narasi keagamaan dan budaya yang dijadikan senjata untuk membenarkan pengucilan dan dominasi teritorial. Artikel ini mengeksplorasi peran Islam Kemanusiaan yang diusung oleh Nahdlatul Ulama (NU) Indonesia dan KTT Internasional Otoritas Keagamaan R20 (ISORA) dalam menawarkan kerangka teologis dan sosial untuk menengahi konflik ini. Dengan menekankan kasih sayang universal (rahmah) dan kewarganegaraan yang setara (al-muwatinun), Islam Kemanusiaan melawan narasi suci yang memecah belah guna mendorong pembangunan perdamaian yang berlandaskan martabat manusia. Menggunakan pendekatan analitis kualitatif, penelitian ini mengkaji mekanisme rekontekstualisasi dalam yurisprudensi Islam (fiqh) yang diterapkan pada krisis Palestina. Studi ini berpendapat bahwa dengan membongkar kategori hukum yang usang seperti kafir (infidel) dan menyelaraskan keyakinan dengan Piagam PBB, Islam Kemanusiaan menyediakan alternatif yang berkelanjutan bagi model perdamaian teknokratis.